Обґрунтування енергетичного аналізу системи «Фотомодуль ‒ акумулятор» - Коробка, Сергій Васильович; Болтянський, Борис Володимирович; Скляр, Радміла Вікторівна; Стукалець, Ігор Геннадійович; Шеремета, Роман Богданович; Korobka, Sergiy; Boltianskyi, Boris; Skliar, Radmila; Stukalets, Ihor; Sheremeta, Roman (Запоріжжя : ТДАТУ, Видавничій дім "Гельветика", 2025)
UA: У роботі здійснено аналіз впливу параметрів зарядно-розрядного процесу на енергетичну ефективність акумуляторів. Порівнюючи навантажувальні характеристики типового фотомодуля із зарядними характеристиками акумулятора, визначено основні причини втрат ефективності у фотоелектричних установках. Отримані закономірності необхідно враховувати під час проєктування структури фотоелектричних установок і розроблення алгоритмів їх функціонування для максимально ефективного використання сонячної енергії. /// EN: The paper analyzes the influence of the parameters of the charge-discharge process on the energy efficiency of batteries. By comparing the loading characteristics of a typical photomodule with the charging characteristics of a battery, the main reasons for efficiency losses in photovoltaic installations have been determined. The obtained regularities must be taken into account when designing the structure of photovoltaic installations and developing algorithms for their operation for the most efficient use of solar energy. Addressing the urgent need for sustainable solutions to mitigate the environmental impacts of batteries highlights the critical importance of developing a mechanism to manage the large number of batteries reaching the end of their first life cycle. While secondary-use batteries have clear advantages, the reuse of cation-based secondary-use batteries poses certain challenges. A variety of challenges require our attention and creative approach, but overcoming these challenges often leads to innovation and progress in the field. This study examines the associated complexities and challenges in detail to understand the reality and potential barriers. Combining individual methods or using hybrid approaches to optimize the efficiency of the evaluation process can be considered as a promising strategy. Battery research is still in its infancy, with further developments expected in the coming years to address existing gaps. A key aspect of addressing these gaps is gaining a deeper understanding of battery degradation processes in different chemical environments, which is critical to addressing issues that affect long-term battery performance, reliability, and stability over extended periods of operation. These advances will certainly impact performance and environmental aspects, as well as potential benefits of secondary use, which will require further research, including impact and battery life cycle assessments.
Justification of the energy analysis of the photomodule-battery system
Keywords: фотомодуль; фотоелектрична установка; акумулятор; зарядний струм; зарядна напруга; ефективність; коефіцієнт віддачі; коефіцієнт корисної дії; photomodule; photovoltaic installation; battery; charging current; charging voltage; efficiency